Natural Reserves and Sustainable Development of AL- Tayeb Reserve / South Iraq: A Review Article - Ali Mohammed Abdullah; Abdullah Salim Al- Karawi; Omer Abdul Kareem Aswad; Alia Essam Alubadi; Estabraq Mohammed Ati; Dr. Reyam Naji Ajmi (Global Scientific Publishing, 2023)
The ability of Iraq to develop its natural reserves and forests to protect natural diversity and save unique wild animals and plants from extinction is discussed in this article. Monitoring living things helps to ensure their sustainability and prevents extinction in the southern Iraq reserve. There are plant and animal species in reserves that are either endangered or invasive aliens, and their reaction to unfamiliar environments as it included, is very important. The management of living natural resources is considered by adopting practices that will integrate Biodiversity conservation needs and development priorities through diversity issues. the issue with a review essay following the Iraqi environment's various aggravating issues, As a result, environmental contamination that affected the majority of environmental factors began to emerge. This had a detrimental effect on biodiversity and sustainable development in the environment, particularly in natural reserves. The main goal was to clarify the idea of a system of natural reserves and biodiversity, as well as to promote sustainable management of living natural resources by implementing practices that would achieve integration between the demands of biodiversity conservation and development priorities in a methodical manner by reviewing sources, conducting research, and gathering pertinent data. Important recommendations and suggestions for the development of Al-Tayeb Natural Reserve in Maysan, southern Iraq, are provided by international assessments and officially sanctioned statistics.
Keywords: Natural reserves; Al-Tayeb reserves; Sustainable development